Oi cat Oi Frog and Friends - Gray;Res; Field;Jim (Great Britain Hachette Children's, 2019)
According to Frog ... Cats sit on gnats, Dogs sit on logs, Alpacas sit on cream crackers, Armadillos sit on pillows and Chicks sit on bricks. But wait! Cat doesn't like sitting on gnats, they keep biting his bottom! Will Frog and Dog help him change the rules? 'This animal rhyming silliness goes from strength to strength.' The Guardian 'Will have children in fits of giggles.' Parents in Touch